Characterization of rice genotypes used in Brazil regarding salinity tolerance at the seedling stage - Oliveira, Victoria Freitas de; Maltzahn, Latóia Eduarda; Viana, Vívian Ebeling; Venske, Eduardo; Maia, Luciano Carlos da; Oliveira, Antonio Costa de; Pegoraro, Camila (Revista de Ciências Agroveterinárias, 2022)
Rice production (Oryza sativa L.) is among the most economically important activities in the world. However, soil and salinity coming from irrigation water reduce rice yield. Therefore, the identification and/or development of salt-tolerant rice genotypes is a strategy to minimize this problem. The development of new genotypes depends on the presence of genetic diversity, and understanding the heritability of a desired trait can help in the selection process. Thus, this study aimed to identify superior genotypes, analyze the genetic diversity and estimate the heritability for salinity tolerance at the seedling stage in rice genotypes used in Brazil. For this, seedlings of 69 genotypes were kept in hydroponic solution with 40 mM NaCl (4 dSm-1) for seven days. Shoot length, root length, shoot dry weight, and root dry weight) were evaluated and the results were converted into relative performance. Tolerant and moderately salt-tolerant genotypes were identified at the seedling stage, which can be used in breeding programs and can be cultivated in high salinity areas. Principal component analysis showed the presence of genetic diversity for salinity response. Finally, it was shown that most of the observed variation is of genetic origin, which can make the breeding process less difficult.